2019
DOI: 10.1247/csf.18030
|View full text |Cite
|
Sign up to set email alerts
|

PUM2 Promotes Glioblastoma Cell Proliferation and Migration via Repressing BTG1 Expression

Abstract: PUM2, an RNA binding protein, is known to promote stem cell proliferation via repressing expressions of cell cycle genes. Similar with stem cells, malignant cells are characterized by unlimited proliferation and remote migration. However, roles of PUM2 in cancer development are controversial. Here, we investigated PUM2's role in glioblastoma development and its relationship with the cell cycle regulator BTG1. Immunoblotting and RT-qPCR were used to evaluate protein expression level and transcript level, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…PUM2 enhanced the stemness of breast cancer cells by interacting with NRP-1 (38). Knockdown of PUM2 suppressed the proliferation and invasion of glioblastoma cells by regulating BTG1 expression (42). Moreover, PUM2 has also been revealed to be involved in the progression of osteosarcoma (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PUM2 enhanced the stemness of breast cancer cells by interacting with NRP-1 (38). Knockdown of PUM2 suppressed the proliferation and invasion of glioblastoma cells by regulating BTG1 expression (42). Moreover, PUM2 has also been revealed to be involved in the progression of osteosarcoma (45).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the predicted top 5 miRNAs were verified by luciferase reporter activity assay, and 3 miRNAs including PUM2 were revealed to be downregulated by miR-376a-3p. Thirdly, PUM2 was reported to promote cell proliferation and metastasis in several cancer types (38,42). However, the other 2 miRNAs were not reported to be involved in cancer pathology and were therefore not selected.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found associations between BTG1 and various tumors. It has been shown to be abnormally expressed in gastric cancer, kidney cancer, hepatocellular carcinoma, thyroid carcinoma, nasopharyngeal carcinoma, ovarian cancer, breast cancer, non-small cell lung cancer, glioblastoma and cervical cancer [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, deregulated expression of Btg1 is involved in gastric (15), kidney (16), liver (17), thyroid (18), nasopharyngeal (19), ovarian (20), breast (21,22), and non-small-cell lung cancers (23), and is frequently associated with disease severity. Notably, although Btg1 is expressed in the developing and adult brain (11,(24)(25)(26), its involvement in brain tumors has been investigated only in gliomas (27,28).…”
Section: Introductionmentioning
confidence: 99%